Mappings and decompositions of pairwise continuity on (i, j)-almost Lindelof and (i, j)-weakly Lindelof spaces - Salleh, Zabidin; Kilicman, Adem (Universidad Catolica del Norte, 2021)
The purpose of this paper is to study the eect of mappings and some decompositions of pairwise continuity on (i, j)-almost Lindelöf spaces and (i, j)-weakly Lindelöf spaces. The main results are that an (i, j)-continuous image of an (i, j)-almost Lindelöf space is (i, j)-almost Lindelof and a pairwise almost continuous image of an (i, j)-weakly Lindelöf space is (i, j)-weakly Lindelöf. We also show that (i, j)-almost Lindelöf, pairwise almost Lindelöf, (i, j)-weakly Lindelöf and pairwise weakly Lindelöf properties are bitopological properties.